2019
DOI: 10.1016/j.foodchem.2019.05.092
|View full text |Cite
|
Sign up to set email alerts
|

Cooking effects on bioaccessibility of chlorophyll pigments of the main edible seaweeds

Abstract: Edible seaweeds are highly consumed food with a rich chlorophyll profile. Although seaweeds are mainly cooked ingested, the influence of cooking on the chlorophyll bioaccessibility remains unknown. In this research, cooked Nori, Sea Lettuce and Kombu were subjected to an in vitro digestion and following micellarization investigations. The processing of red seaweed does not affect the chlorophyll recovery, while cooking green and brown seaweeds implies an important 2 increase in chlorophyll recovery after in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…However, in contrast to the carotenoid studies, knowledge is limited regarding the yield of chlorophyll metabolites, their absorption and transportation processes, their metabolic pathways, and their precise oxidation mechanisms. At the in vitro level, only few researchers have studied the stability of chlorophylls during digestion [ 153 , 154 , 155 , 156 , 157 ] and subsequent absorption through intestinal cells [ 153 , 154 , 155 , 157 , 158 ]. The major outcome is that chlorophylls a and b are transformed into their corresponding pheophorbides and pheophytins and are absorbed at similar rates as carotenoids.…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to the carotenoid studies, knowledge is limited regarding the yield of chlorophyll metabolites, their absorption and transportation processes, their metabolic pathways, and their precise oxidation mechanisms. At the in vitro level, only few researchers have studied the stability of chlorophylls during digestion [ 153 , 154 , 155 , 156 , 157 ] and subsequent absorption through intestinal cells [ 153 , 154 , 155 , 157 , 158 ]. The major outcome is that chlorophylls a and b are transformed into their corresponding pheophorbides and pheophytins and are absorbed at similar rates as carotenoids.…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
“…exhibit significantly lower antiradical capacity than metallo-derivatives, with the presence of copper being more favorable than zinc or magnesium. It has been hypothesized [ 148 , 157 ] that the presence of the metal could increase the electron density at the center of the skeleton, thereby enhancing the ability of the conjugated porphyrin backbone to donate electrons. An additional explanation is based on the ability of the π-cation radical in the porphyrin structure to induce the donation of electrons from the porphyrin structure in order to break the propagation of the radical chain process [ 166 ].…”
Section: Antioxidant Capacity Of Chlorophyllsmentioning
confidence: 99%
“…The bioaccessibility and bioavailability of carotenoids are widely evaluated in different food sources, emphasizing mainly on fruits and vegetables (Reboul et al 2006;O'Connell et al, 2007;Chitchumroonchokchai and Failla, 2017 2017; Rodrigues et al, 2017;Murador et al, 2021;Nascimento et al, 2021). In parallel, chlorophylls have few studies found in the literature, although a significant advance has taken place in recent years (Ferruzzi and Blakeslee, 2007;Gallardo-Guerrero et al, 2008;Gandul-Rojas et al, 2009;Chen and Roca, 2018a;Chen and Roca, 2019). In turn, a wide range of bioaccessibility and bioavailability values can be found in the literature for the same compound.…”
Section: )mentioning
confidence: 99%
“…Although recognized as potential sources of these biocompounds, to the best of our knowledge, regrettably, there is no evidence of bioaccessibility and absorption of chlorophylls from microalgae. The available information on bioaccessibility and bioavailability of chlorophylls and their derivatives is limited and are based on in vitro assays with higher food matrix plants (Ferruzzi et al, 2001;Gallardo-Guerrero et al, 2008;Hayes et al, 2020), edible seaweeds (Chen and Roca, 2018a;Chen and Roca, 2018b;Chen and Roca, 2019) and some chlorophyll standards (Gandul-Rojas et al, 2009). In fact, these biomolecules were considered non-absorbable by our body, and only in the last few decades have studies proven the absorption of these compounds (Ferruzzi and Blakeslee, 2007).…”
Section: )mentioning
confidence: 99%
“…Generally TLC technique can be utilized to separate metal derivatives (M = Cu, Zn, Fe) of chlorophylls and chlorophyllins extracted from vegetable and fruits using ethanol and segregated against n-butyl acetate from chewing gum using ethanol, n-butyl acetate, and in addition hot water prior to filtration. A similar procedure has been used to the study of candies, chewing gum, processed seaweeds, chocolate and processed edible wild plants, and in boiled bracken, agar agar, and chewing gum [121]. Scotter et al (2005) determined Na-Cu-Chl (E141(i) and E141(ii)) from dried soup mixes, jellies, boiled sweets, biscuits and flour confectionery against the artificial dye Solvent Green 3 as internal standard using mobile phase phosphate buffer (pH 2.6) and ethyl acetate: acetone can be used as mobile phase (under gradient elution) using RP-HPLC equipped with both DAD and FLD detection [59].…”
Section: Cu-chlorophylls (E141(i) and Cu-chlorophyllins (E141(ii))mentioning
confidence: 99%